European Surveillance System on Contact Allergies (ESSCA): polysensitization, 2009-2014 - Dittmar, Daan; Uter, Wolfgang; Bauer, Andrea; Fortina, Ana B.; Bircher, Andreas; Czarnecka-Operacz, Magdalena; Dugonik, Aleksandra; Elsner, Peter; Gallo, Rosella; Ghaffar, Sharizan A.; Giménez-Arnau, Anna; Johnston, Graham A.; et al. (Contact dermatitis, 2018)
Background: Polysensitization, defined as being allergic to three or more haptens from the European baseline series, is considered to reflect increased susceptibility to developing a contact allergy, and is likely to be associated with an impaired quality of life. Objectives To evaluate the prevalences of polysensitization across Europe and to analyse factors associated with polysensitization. Methods Patch test data collected by the European Surveillance System on Contact Allergies (ESSCA; www.essca-dc.org) in consecutively patch tested patients from January 2009 to December 2014, comprising 11 countries and 57 departments, were retrospectively analysed. Results A total of 86 416 patients were available for analysis, showing a standardized prevalence of polysensitization of 7.02%, ranging from 12.7% (Austria) to 4.6% (Italy). Allergen pairs with the strongest association are reported for the total population, for South Europe, and for North/Central Europe. Overall, polysensitized patients showed a higher percentage of extreme (+++) positive patch test reactions than oligosensitized patients. Female sex, occupational dermatitis and age > 40 years were risk factors for polysensitization. Conclusions The varying prevalences of polysensitization across Europe most likely reflect differences in patient characteristics and referral patterns between departments. Known risk factors for polysensitization are confirmed in a European dermatitis population.
Gesehen am 17.03.2020